Biomass nanofiber-induced one-dimensional ordered bead string-shaped non-noble metal oxygen reduction catalyst and preparation method and application thereof
Patent Information
- Application Number
- CN202611379303.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]针对现有ZIF–8衍生Fe–N–C催化剂存在颗粒松散堆积、高温煅烧阶段易烧结团聚、催化层缺少连续骨架支撑、动态工况之下结构容易坍塌、耐久性能较差的技术缺陷,本发明提供一种生物质纳米纤维诱导的一维有序珠串状非贵金属氧还原催化剂及其制备方法和应用
[0028]1、本发明以生物质纳米纤维作为诱导模板,通过其表面丰富的含氧官能团与金属离子的配位相互作用,诱导含铁ZIF-8前驱体沿纤维长度方向定向成核并有序串联生长,经高温热解后形成碳化纤维为骨架、Fe–N–C颗粒为珠串单元的一维有序珠串状结构。该结构设计彻底改变了传统Fe–N–C催化剂颗粒三维无序松散堆积的形貌,从根本上解决了高温煅烧阶段颗粒易烧结团聚、孔道塌陷闭塞的难题,保障了颗粒内部微孔的敞开状态和Fe–Nx活性位点的可及性。
Smart Images

Figure CN122992095A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of non-precious metal catalysts for fuel cells, specifically relating to a one-dimensional ordered beaded non-precious metal oxygen reduction catalyst induced by biomass nanofibers, its preparation method, and its application. Background Technology
[0002] Proton exchange membrane fuel cells (PEMFCs), as efficient and clean electrochemical energy conversion devices, have broad application prospects in transportation, distributed power generation, and portable power sources. However, the oxygen reduction reaction (ORR) kinetics at the PEMFC cathode are slow, and traditional cathode catalysts are highly dependent on platinum-based precious metal materials. The scarcity and high cost of platinum, coupled with its susceptibility to poisoning and deactivation under certain operating conditions, severely restrict the large-scale commercialization of PEMFCs. Therefore, developing low-cost, highly active, and highly stable non-precious metal oxygen reduction catalysts has become a research hotspot in the fuel cell field.
[0003] In recent years, metal-organic framework (MOF) derived Fe–N–C catalysts have gained attention due to their atomically dispersed Fe–N x Active sites, high specific surface area, and tunable pore structure make them highly promising alternatives to non-platinum oxygen reduction catalysts. Among them, ZIF-8 has become the preferred precursor for preparing high-performance Fe-N-C catalysts due to its nitrogen-rich framework, three-dimensional pore structure that can induce uniform dispersion of Fe atoms, and the ability to further create pores after Zn volatilization.
[0004] However, conventional ZIF-8 derived Fe–N–C catalysts are prone to sintering and agglomeration during high-temperature pyrolysis, leading to pore blockage and the release of large amounts of Fe–N. x The active sites are enclosed in closed pores, significantly reducing their utilization. When the cathode catalyst layer is prepared using these disorderedly stacked particles, continuous conductive channels cannot be formed between the particles, resulting in low mass transfer efficiency. Furthermore, the catalyst layer lacks a continuous, through-type framework support, and its structural stability relies solely on the loose physical contact between particles. Under PEMFC dynamic operating conditions, the potential fluctuations caused by frequent start-ups and load switching, along with the acidic environment, further induce demetallization of Fe active species and corrosion of the carbon support, leading to catalyst layer structural collapse, irreversible loss of active sites, and membrane electrode output performance far lower than the three-electrode test results, making it difficult to meet the durability requirements for long-term service.
[0005] To address the above problems, this invention is proposed. Summary of the Invention
[0006] To address the technical shortcomings of existing ZIF-8 derived Fe-N-C catalysts, such as loose particle packing, easy sintering and agglomeration during high-temperature calcination, lack of continuous skeletal support in the catalyst layer, easy structural collapse under dynamic operating conditions, and poor durability, this invention provides a biomass nanofiber-induced one-dimensional ordered beaded non-precious metal oxygen reduction catalyst, its preparation method, and its application.
[0007] This invention uses biomass nanofibers as an inducing template to promote the orderly growth of iron-containing ZIF-8 precursors along the fiber length. After high-temperature pyrolysis, a continuous framework is formed by carbonized fibers, and Fe-N-C particles derived from the iron-containing ZIF-8 precursors serve as bead-like units, collectively constructing a one-dimensional ordered bead-like structure. The carbonized fibers act as a continuous conductive backbone connecting all particles, establishing a long-range electron transport pathway. This confined arrangement along the fiber length changes the traditional three-dimensional disordered stacking and large-area adhesion of Fe-N-C particles, inhibiting sintering and agglomeration and pore collapse during calcination, ensuring that the micropores inside the particles remain open, and improving the Fe-N-C nanofiber structure. x Accessibility of active sites. At the same time, Fe–N–C particles are strung together on the fiber skeleton, which overcomes the shortcoming that the catalyst layer relies solely on physical contact between particles to maintain its structure. This can suppress particle migration, shedding, and demetallization of active sites under dynamic operating conditions of fuel cells, significantly improve the long-term service stability of membrane electrode assembly, and narrow the gap between three-electrode testing and actual membrane electrode performance.
[0008] The present invention solves the technical problem by adopting the following technical solution:
[0009] The first aspect of this invention provides a one-dimensional ordered beaded non-noble metal oxygen reduction catalyst induced by biomass nanofibers. The catalyst possesses a one-dimensional ordered beaded morphology: carbonized biomass nanofibers serve as a one-dimensional continuous supporting framework, with porous Fe–N–C nanoparticles arranged in an ordered series along the fiber length direction; the porous Fe–N–C nanoparticles have a framework composed of Fe, N, and C elements, with Fe coordinated with N in an atomically dispersed manner to form Fe–N x Structural unit, the Fe–N x The structural unit is the intrinsic building block that makes up the skeleton.
[0010] Preferably, the Fe–N x The structural units constitute the catalytic active sites of the porous Fe–N–C nanoparticles.
[0011] Preferably, the biomass nanofibers are selected from any one of bacterial cellulose nanofibers, cellulose nanocrystals, and cellulose nanofibers.
[0012] Preferably, the one-dimensional ordered beaded morphology is completely preserved after high-temperature pyrolysis, and the porous Fe–N–C nanoparticles have a particle size of 80–180 nm.
[0013] A second aspect of this invention provides a method for preparing the biomass nanofiber-induced one-dimensional ordered beaded non-noble metal oxygen reduction catalyst described in the first aspect, comprising the following steps:
[0014] (1) The biomass nanofibers were dispersed in methanol and ultrasonically dispersed to obtain a biomass nanofiber dispersion.
[0015] (2) Add zinc source and iron source to the biomass nanofiber dispersion and stir until completely dissolved; utilize the selective coordination and capture effect of oxygen-containing functional groups on the surface of biomass nanofibers to make zinc ions anchored in series along the fiber length direction to obtain biomass nanofiber dispersion A with zinc ion sites fixed on the surface.
[0016] (3) Dissolve the imidazole ligand in methanol to obtain solution B;
[0017] (4) The solution B is added to the dispersion A and reacted at room temperature; the imidazole ligand coordinates with the zinc ion site to form ZIF-8 crystals in situ at the zinc ion site, and the ZIF-8 crystals are arranged in series along the fiber length to form a beaded string; during the growth of ZIF-8 crystals, the iron source in the solution enters the ZIF-8 cavity or channel to obtain a one-dimensional ordered beaded string of iron-containing ZIF-8 precursor biomass nanofiber composite material.
[0018] (5) After centrifugation, washing with methanol, and drying of the biomass nanofiber composite material containing the one-dimensional ordered beaded iron ZIF-8 precursor obtained in step (4), it is placed in an inert atmosphere for high-temperature pyrolysis. The one-dimensional ordered beaded morphology is maintained during the high-temperature pyrolysis process. The biomass nanofibers are carbonized to form a one-dimensional continuous support framework. The iron ZIF-8 precursor is pyrolyzed into porous Fe-N-C nanoparticles, thus obtaining the one-dimensional ordered beaded non-precious metal oxygen reduction catalyst.
[0019] Preferably, the zinc source in step (2) is zinc nitrate hexahydrate, and the iron source is iron acetylacetone; the imidazole ligand in step (3) is 2-methylimidazole.
[0020] Preferably, the molar ratio of the iron source to the zinc source in step (2) is 1:30 to 1:50; and the molar ratio of the zinc source to the imidazole ligand in step (3) is 1:6 to 1:10.
[0021] Preferably, the in-situ reaction in step (4) is carried out at a temperature of 20-30°C for 2-4 hours.
[0022] Preferably, the high-temperature pyrolysis in step (5) is as follows: under a nitrogen or argon atmosphere, the temperature is raised to 800-1100°C at a heating rate of 3-10°C / min and held at a constant temperature for 1-3 hours.
[0023] In this invention, oxygen-containing functional groups (such as hydroxyl groups) on the surface of biomass nanofibers selectively coordinate and capture zinc ions, causing zinc ions to form an ordered array of anchoring sites along the fiber length. When imidazole ligands are added, heterogeneous nucleation occurs only at these anchored zinc ion sites, forming ZIF-8 crystals in situ, which then grow in a confined manner along the fiber length, ultimately forming a one-dimensional ordered beaded structure.
[0024] During this process, the iron source (ferric acetylacetone) is uniformly dispersed in the reaction system in molecular form. Because it is in a coordination-saturated state in the room-temperature methanol system, it does not dissociate into free iron ions and therefore does not participate in the selective anchoring competition of oxygen-containing functional groups on the fiber surface for zinc ions. As the ZIF-8 crystal grows, the iron source simultaneously enters the ZIF-8 cavity or channel, occupying some coordination sites and forming an iron-doped iron-containing ZIF-8 precursor.
[0025] During high-temperature pyrolysis, the organic ligands in the ZIF-8 framework carbonize and transform into a nitrogen-doped carbon framework. Simultaneously, the zinc component volatilizes and escapes as vapor, leaving numerous nodal vacancies in the carbon framework. Iron pre-doped into the ZIF-8 framework migrates to these nodal vacancies at high temperatures and coordinates with neighboring nitrogen atoms, forming Fe–N atoms in an atomically dispersed manner. x Structural unit, Fe–N x The structural unit is the intrinsic building block that constitutes the carbon skeleton. Thus, the carbonization of biomass nanofibers forms a one-dimensional continuous supporting skeleton, and the pyrolysis of the iron-containing ZIF-8 precursor is transformed into porous Fe-N-C nanoparticles, while the one-dimensional ordered beaded morphology is completely maintained during the pyrolysis process.
[0026] The third aspect of this invention provides the application of the biomass nanofiber-induced one-dimensional ordered beaded non-precious metal oxygen reduction catalyst described in the second aspect in the preparation of the cathode catalyst layer and membrane electrode assembly of a proton exchange membrane fuel cell.
[0027] The present invention has the following beneficial effects:
[0028] 1. This invention uses biomass nanofibers as an inducing template. Through the coordination interaction between the abundant oxygen-containing functional groups on their surface and metal ions, it induces the directional nucleation and orderly tandem growth of iron-containing ZIF-8 precursors along the fiber length. After high-temperature pyrolysis, a one-dimensional ordered beaded structure is formed with carbonized fibers as the framework and Fe–N–C particles as beaded units. This structural design completely changes the morphology of the traditional three-dimensional disordered and loosely packed Fe–N–C catalyst particles, fundamentally solving the problems of easy sintering and agglomeration of particles and pore collapse and blockage during high-temperature calcination, ensuring the open state of the micropores inside the particles and the Fe–N… x Accessibility of active sites.
[0029] 2. In this invention, carbonized biomass nanofibers serve as a one-dimensional continuous conductive framework throughout the entire catalytic material, connecting discrete Fe–N–C particles in series. This establishes a long-range continuous electron transport pathway within the catalytic layer, significantly improving the mass transfer efficiency of electrons, protons, reactant gases, and generated water. It also increases the effective gas-liquid-solid three-phase reaction interface, which is beneficial for fully utilizing the catalytic efficiency of each Fe–N–C particle. More importantly, the one-dimensional ordered beaded structure confines the Fe–N–C particles along the fiber length direction, and the fiber framework provides physical barrier properties, inhibiting particle migration, agglomeration, and sintering during high-temperature calcination and long-term operation. Simultaneously, Fe–N… x As the intrinsic building blocks of the carbon skeleton, the structural units are structurally constrained during pyrolysis and operation, fundamentally inhibiting the aggregation and demetallization of active sites. Furthermore, the particles are strung together on the carbon fiber skeleton, forming stable connections. This eliminates the reliance on loose physical contact between particles to maintain the overall structure of the catalyst layer, effectively suppressing particle shedding and demetallization of active sites under dynamic operating conditions. These structural advantages collectively endow the catalyst with excellent long-term service stability at the membrane electrode assembly level, narrowing the gap between three-electrode testing and actual membrane electrode performance.
[0030] 3. This invention uses biomass nanofibers as an inducing template, which are widely available, renewable, and inexpensive, aligning with green and sustainable development requirements. Furthermore, the preparation method is simple, operates under mild conditions (room temperature reaction, conventional pyrolysis), requires no complex equipment or template removal steps, and is easily scaled up for mass production, demonstrating promising industrial application prospects. The resulting catalyst exhibits excellent oxygen reduction catalytic activity and stability in acidic media, and can be widely used in the preparation of cathode catalyst layers and membrane electrode assemblies for proton exchange membrane fuel cells, providing a new approach for the design of low-cost, high-performance non-precious metal oxygen reduction catalysts. Attached Figure Description
[0031] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0032] Figure 1 This is a scanning electron microscope (SEM) image of the one-dimensional ordered beaded non-precious metal oxygen reduction catalyst induced by biomass nanofibers prepared in Example 1 of the present invention.
[0033] Figure 2 The image shows a scanning electron microscope (SEM) image of the template-free Fe–N–C catalyst prepared in Comparative Example 1.
[0034] Figure 3 The image shows a scanning electron microscope (SEM) image of the Fe–N–C@CNT catalyst prepared according to the conditions of CN117727956A in Comparative Example 3.
[0035] Figure 4 This is a comparison of the polarization curves and power density curves before and after the square wave acceleration durability test (AST) of the catalysts prepared in Example 1(a) and Comparative Example 1(b) of the present invention in the membrane electrode assembly.
[0036] Figure 5 The polarization curves and power density curves before and after the square wave accelerated durability test (AST) of the Fe–N–C@CNT catalyst prepared according to the conditions of CN117727956A in the membrane electrode assembly are shown for Comparative Example 3.
[0037] Figure 6 The image shows a scanning electron microscope (SEM) image of the catalyst prepared in Example 1 of this invention after a square wave acceleration durability test.
[0038] Figure 7 The image shows a scanning electron microscope (SEM) image of the template-free Fe–N–C catalyst prepared in Comparative Example 1 after a square wave acceleration durability test. Detailed Implementation
[0039] The present invention will be further described below through embodiments, but is not limited to these embodiments. Experimental methods not specifically described in the embodiments generally use conventional conditions and conditions described in manuals, or conditions recommended by the manufacturer. The general equipment, materials, reagents, etc., used are all commercially available unless otherwise specified.
[0040] Example 1
[0041] Precursor synthesis:
[0042] 30 mg of lyophilized bacterial cellulose (BC, diameter 20–50 nm) was dispersed in 50 mL of methanol and sonicated at 200–400 W for 10–30 min to form a uniform milky white dispersion. 0.5 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O, approximately 1.68 mmol) was added to the dispersion and stirred until completely dissolved. Then, 15 mg of ferric acetylacetone (Fe(acac)3, approximately 0.042 mmol) was added and stirred until completely dissolved to obtain dispersion A (Fe / Zn molar ratio ≈ 0.025).
[0043] Dissolve 1.1 g of 2-methylimidazole (approximately 13.4 mmol, Zn / imidazole molar ratio ≈ 0.13) in 50 mL of methanol and stir until completely dissolved to obtain solution B.
[0044] Solution B was rapidly added to dispersion A and allowed to stand at 25°C for 3 hours. During the reaction, the zinc and iron sources underwent in-situ coordination with 2-methylimidazole to generate an iron-containing ZIF-8 precursor. The abundant oxygen-containing functional groups on the surface of bacterial cellulose provided numerous nucleation sites, inducing the precursor to nucleate directionally on the fiber surface and grow in series along the fiber length, forming a one-dimensional ordered beaded structure.
[0045] After the reaction was completed, the solid product was collected by centrifugation, washed three times with methanol, and dried under vacuum at 60°C for 12 hours to obtain a bacterial cellulose composite material loaded with one-dimensional ordered beaded iron-containing ZIF-8 precursor.
[0046] Pyrolysis treatment:
[0047] The above precursor was placed in a tube furnace and heated to 1100°C at a heating rate of 5°C / min under an argon atmosphere (flow rate 30 sccm), held for 1 hour, and then naturally cooled to room temperature to obtain a one-dimensional ordered beaded Fe–N–C oxygen reduction catalyst (denoted as 1D Fe–N–C@BC).
[0048] Structural characterization:
[0049] The obtained catalyst exhibits a one-dimensional ordered bead-like morphology. Figure 1 The carbonized bacterial cellulose nanofibers (approximately 50-100 nm in diameter) form a one-dimensional continuous support framework, with Fe–N–C nanoparticles arranged in an orderly series along the fiber length, forming bead strings with a diameter of approximately 100-150 nm. This bead-like morphology remained intact after pyrolysis at 1100°C, without any obvious structural collapse or disordered aggregation.
[0050] Example 2
[0051] Cellulose nanocrystals (CNC, diameter 10–30 nm, length 100–500 nm) were used instead of BC, in the same amount as in Example 1 (30 mg based on lyophilized mass), and all other conditions were the same as in Example 1. The resulting catalyst exhibited a one-dimensional beaded morphology (similar to Example 1). Figure 1 (Similarly), the diameter of the beaded strands is approximately 80–120 nm.
[0052] Example 3
[0053] Cellulose nanofibers (CNF, diameter 5–20 nm) were used instead of BC, and the amount used was the same as in Example 1 (30 mg based on lyophilized mass), with the other conditions being the same as in Example 1.
[0054] The resulting catalyst has a one-dimensional beaded structure (and) Figure 1 Similarly, the diameter of the beaded string is approximately 90–130 nm (denoted as 1DFe–N–C@CNF).
[0055] Example 4
[0056] Sodium carboxymethyl cellulose (CMC, molecular weight 700,000, degree of substitution DS=0.9, viscosity 2500–4500 mPa·s) was used instead of BC, and the amount used was the same as in Example 1 (30 mg based on lyophilized mass), and the other conditions were the same as in Example 1.
[0057] The resulting catalyst has a one-dimensional beaded structure (and) Figure 1 Similarly, the size distribution of the bead strands is approximately 80–180 nm (denoted as 1D Fe–N–C@CMC).
[0058] Comparative Example 1
[0059] No biomass nanocellulose template was used; all other conditions were the same as in Example 1.
[0060] 1.1 g of 2-methylimidazole was dissolved in 50 mL of methanol (solution A), and 15 mg of iron acetylacetone (Fe(acac)3) and 0.5 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) were dispersed in 50 mL of methanol (solution B). Solution B was mixed with solution A and reacted at 25°C for 3 hours. After the reaction was completed, the mixture was centrifuged, washed with methanol, and dried under vacuum at 60°C to obtain the iron-containing ZIF–8 precursor.
[0061] The precursor was placed in a tube furnace and heated to 1100°C at a rate of 5°C / min under an argon atmosphere (flow rate 30 sccm), held for 1 hour, and then naturally cooled to obtain the Fe–N–C catalyst (denoted as Fe–N–C).
[0062] The obtained sample has a disordered granular morphology. Figure 2The Fe–N–C particles were randomly packed together, with obvious adhesion and sintering between them, and no bead-like structure was observed.
[0063] Comparative Example 2
[0064] 30 mg of anhydrous FeCl3 (calculated as anhydrous) was ultrasonically dispersed with 200 mg of Ketjen Black and 2 g of dicyandiamide (as nitrogen source and auxiliary carbon source) in 50 mL of ethanol. After stirring for 2 hours, the mixture was stirred and evaporated to dryness at 60°C to obtain the Fe / KB precursor.
[0065] The precursor was placed in a tube furnace and heated to 1100°C at a rate of 5°C / min under an argon atmosphere. The temperature was held for 1 hour and then allowed to cool naturally to obtain the Fe–N–KB catalyst.
[0066] The obtained sample is a disordered structure of Fe–N–C particles supported on the surface of Ketjen black.
[0067] Comparative Example 3
[0068] A control sample (denoted as Fe–N–C@CNT) was prepared by replicating the conditions of Example 1 in the applicant's prior patent CN117727956A, for structural and performance comparison:
[0069] 0.5 g FeCl3·6H2O, 1.2 g Zn(NO3)2·6H2O, and 0.5 g carbon nanotubes (CNTs, 20–50 nm in diameter and 10–20 μm in length) were dispersed in 150 mL of methanol. Then, 100 mL of a methanol solution containing 2.5 g 2-methylimidazole was added, and the mixture was reacted at 25°C for 12 hours. After the reaction was complete, the mixture was centrifuged, washed, and dried to obtain the precursor.
[0070] The precursor was placed in a tube furnace and heated to 900°C at a rate of 5°C / min under an argon atmosphere (30 sccm), held for 2 hours, and then naturally cooled to obtain the Fe–N–C@CNT catalyst.
[0071] The obtained sample is a three-dimensional interconnected network structure of carbon nanotubes and Fe–N–C particles. Figure 3 No beaded appearance was observed.
[0072] Test Example 1
[0073] Membrane electrode assembly (MEA) testing
[0074] The catalysts obtained in Examples 1-4 and Comparative Examples 1-3 were used to prepare membrane electrode assemblies (MEAs) under the following test conditions:
[0075] Anode: 40 wt% Pt / C (Johnson Matthey), platinum loading 0.1 mg Pt cm –2 (Based on geometric area), I / C ratio (mass ratio of ionomer to carbon support) = 0.89.
[0076] Cathode: Catalysts obtained in Examples 1-4 and Comparative Examples 1-3, with a catalyst loading of 3.0 mg / cm³. –2 (Based on geometric area), I / C ratio = 0.6.
[0077] Membrane material: Gore 15 membrane.
[0078] Test conditions: Test temperature 80°C, relative humidity 100%, anode / cathode gas flow rates H2 / Air 700 / 1700 sccm respectively, back pressure 2 bar (gauge pressure).
[0079] Square wave accelerated durability testing (AST) protocol: test temperature 80°C, gas flow rates H2 / Air 200 / 200 sccm, relative humidity 100%. Single cell voltage was maintained at 0.6 V and open circuit voltage (OCV) for 2.5 s each, with a voltage ramp-up / pull-down transition time of 0.5 s between OCV and 0.6 V. Polarization curves were acquired after AST cycles of 10k, 20k, and 30k.
[0080] Comparison of AST polarization curves and power density curves before and after Example 1 and Comparative Example 1: Figure 4 As shown, the polarization curves and power density curves before and after AST in Comparative Example 3 are as follows: Figure 5 As shown.
[0081] The initial peak power density of the MEA and the attenuation rate after 30k cycles of AST for each embodiment and comparative example are summarized below:
[0082]
[0083] The results show that the one-dimensional ordered beaded Fe–N–C catalysts obtained in Examples 1-4 of this invention are significantly superior to comparative Examples 1-3 in terms of initial MEA performance and durability. Among them, the initial peak power density of the MEA in Example 1 reached 608.1 mW·cm⁻¹. –2 After 30k cycles of square wave AST, the attenuation rate was only 13.5%, indicating that the one-dimensional ordered beaded structure can effectively suppress particle migration, shedding and demetallization of active sites under dynamic operating conditions, and significantly improve the long-term service stability of the catalyst at the membrane electrode assembly level.
[0084] After AST testing, the one-dimensional beaded framework of the catalyst in Example 1 was still clearly discernible. Figure 6While the catalyst in Comparative Example 1 exhibited significant structural collapse and particle agglomeration (), Figure 7 This further verifies the enhancing effect of the one-dimensional ordered beaded structure on the stability of the catalyst layer structure.
[0085] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.
Claims
1. A one-dimensional ordered beaded non-noble metal oxygen reduction catalyst induced by biomass nanofibers, characterized in that, The catalyst possesses a one-dimensional ordered beaded morphology: carbonized biomass nanofibers serve as a one-dimensional continuous supporting framework, with porous Fe–N–C nanoparticles arranged in an ordered series along their fiber length; the porous Fe–N–C nanoparticles have a framework composed of Fe, N, and C elements, with Fe coordinated with N in an atomically dispersed manner to form Fe–N x Structural unit, the Fe–N x The structural unit is the intrinsic building block that makes up the skeleton.
2. The catalyst according to claim 1, characterized in that, The Fe–N x The structural units constitute the catalytic active sites of the porous Fe–N–C nanoparticles.
3. The catalyst according to claim 1, characterized in that, The biomass nanofibers are selected from any one of bacterial cellulose nanofibers, cellulose nanocrystals, and cellulose nanofibers.
4. The catalyst according to claim 1, characterized in that, The one-dimensional ordered beaded morphology is completely preserved after high-temperature pyrolysis, and the porous Fe–N–C nanoparticles have a particle size of 80–180 nm.
5. A method for preparing the biomass nanofiber-induced one-dimensional ordered beaded non-noble metal oxygen reduction catalyst according to any one of claims 1-4, characterized in that, Includes the following steps: (1) The biomass nanofibers were dispersed in methanol and ultrasonically dispersed to obtain a biomass nanofiber dispersion. (2) Add zinc source and iron source to the biomass nanofiber dispersion and stir until completely dissolved; utilize the selective coordination and capture effect of oxygen-containing functional groups on the surface of biomass nanofibers to make zinc ions anchored in series along the fiber length direction to obtain biomass nanofiber dispersion A with zinc ion sites fixed on the surface. (3) Dissolve the imidazole ligand in methanol to obtain solution B; (4) The solution B is added to the dispersion A and reacted at room temperature; the imidazole ligand coordinates with the zinc ion site to form ZIF-8 crystals in situ at the zinc ion site, and the ZIF-8 crystals are arranged in series along the fiber length to form a beaded string; during the growth of ZIF-8 crystals, the iron source in the solution enters the ZIF-8 cavity or channel to obtain a one-dimensional ordered beaded string of iron-containing ZIF-8 precursor biomass nanofiber composite material. (5) After centrifugation, washing with methanol, and drying of the biomass nanofiber composite material containing the one-dimensional ordered beaded iron ZIF-8 precursor obtained in step (4), it is placed in an inert atmosphere for high-temperature pyrolysis. The one-dimensional ordered beaded morphology is maintained during the high-temperature pyrolysis process. The biomass nanofibers are carbonized to form a one-dimensional continuous support framework. The iron ZIF-8 precursor is pyrolyzed into porous Fe-N-C nanoparticles, thus obtaining the one-dimensional ordered beaded non-precious metal oxygen reduction catalyst.
6. The preparation method according to claim 5, characterized in that, The zinc source in step (2) is zinc nitrate hexahydrate, and the iron source is iron acetylacetone; the imidazole ligand in step (3) is 2-methylimidazole.
7. The preparation method according to claim 5, characterized in that, The molar ratio of the iron source to the zinc source in step (2) is 1:30 to 1:50; the molar ratio of the zinc source to the imidazole ligand in step (3) is 1:6 to 1:
10.
8. The preparation method according to claim 5, characterized in that, The in-situ reaction described in step (4) is carried out at a temperature of 20-30°C for 2-4 hours.
9. The preparation method according to claim 5, characterized in that, The high-temperature pyrolysis described in step (5) is as follows: under a nitrogen or argon atmosphere, the temperature is raised to 800-1100℃ at a heating rate of 3-10℃ / min and held at a constant temperature for 1-3 hours.
10. The application of the biomass nanofiber-induced one-dimensional ordered beaded non-precious metal oxygen reduction catalyst according to any one of claims 1 to 4 in the preparation of the cathode catalyst layer and membrane electrode assembly of proton exchange membrane fuel cell.
Citation Information
Patent Citations
High-activity three-dimensional interconnected non-noble metal oxygen reduction catalyst and preparation method thereof
CN117727956A
